Civil disobedience during reformation era - Zawiyah Mohd Zain,; Mohammad Agus Yusoff,; Izham Hakimi Hamdi, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
The removal of Anwar Ibrahim as Deputy Prime Minister of Malaysia in September 1998 was a shock to the nation. This is because there were a series of street demonstrations in 1998 until 2001 that gave birth to reformasi (reform) movement. People thought that the dismissal was unfair due to personal conflict between the Prime Minister, Dr. Mahathir and Anwar Ibrahim. The purpose of this paper is to analyze the emergence of civil disobedience during reform movement and to identify the actors involved in mobilizing civil disobedience. The analysis shows what the main reason behind the outbreak of civil disobedience was the result of government actions that weakened democracy through the restriction of political rights and civil liberties. In this respect, the removal of Anwar Ibrahim was only a triggering factor. Furthermore, the actors who were involved in acts of civil disobedience include students, young people, opposition parties, non government organizations (NGOs) and activists. These groups cooperated to seek justice for Anwar Ibrahim and also raised issues related to corruption, cronyism and abuse of power in the government. Consequently, support for the Barisan Nasional (National Front) coalition, especially the United Malays National Organization (UMNO) declined dramatically in the 1999 general election.